Use of Marketing Concept in the System of Administrative Services in Ukraine: Quality, Efficiency, Social Responsibility - Valerii PAVLIUK; Larysa RADKEVYCH; Vadym OSTAPCHUK (Communications of International Proceedings, 2021)
Purpose: This article examines the content and effectiveness of the use of marketing activities in the provision of administrative public authorities. The executive authorities and the local self-government body increase the number of administrative service centers (ASCs) and their list every year. Understanding the service concept of the state as the concept of its service to people, we consider the application of marketing technologies to improve the quality of administrative services, the effectiveness of government agencies in this area and the maximum satisfaction of consumer needs. Methodology: The research is aimed at understanding the content and role of marketing activities in public administration, as well as the features of the application of public marketing. Therefore, the following methods and techniques were used during its implementation: monitoring of the regulatory framework and retrospective review of the development of the system of administrative services, review and analysis of expert opinion, comprehensive and systematic approach, method of assumptions, modeling. Conclusions: The use of marketing technologies in the provision of administrative services has its own characteristics in comparison with marketing activities in business. The state monopoly on the provision of administrative services of the network of centers eliminates the principle of competition, which is inherent in market competition. But the social function of the state and the change of the state concept in the direction of serving the citizen within the modern reform is the main argument for the need to analyze consumers’ needs, clarify their expectations and develop a unique business model that will make customer service convenient, fast, with the maximum respect of all their rights and with minimized expenses. Implications: Awareness of the need for integrated use of marketing tools in the management system of public services allows to develop meaningful and effective models to meet the needs of citizens and the needs of society, correctly identify areas of ASC network, improve customer service and comprehensively improve service technologies.
Keywords: Administrative services; marketing in public administration; improving the efficiency of administrative services; social responsibility.